2002
DOI: 10.1007/bf02574505
|View full text |Cite
|
Sign up to set email alerts
|

Improved antitumor response to isolated limb perfusion with tumor necrosis factor after upregulation of endothelial monocyte-activating polypeptide II in soft tissue sarcoma

Abstract: Background: Experiments with tumor necrosis factor ␣ (TNF) in rodents have shown that a high dose can lead to hemorrhagic necrosis in tumors. Endothelial monocyte-activating polypeptide II (EMAP-II) is a novel tumor-derived cytokine, and its expression increases the TNF-1 receptor on tumor endothelium, enhances the induction of tissue factor on tumor endothelial cells, and has an antiangiogenic effect. It has recently been shown that in vivo sensitivity of tumor vasculature to TNF is determined by tumor produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Its expression appears to increase the TNF receptor on tumor endothelium, and enhance the induction of tissue factor on endothelial cells, resulting in an antiangiogenic effect. It has been shown that in vivo sensitivity of the tumor vasculature to TNF is determined by the tumor production of EMAP‐II 48–50. This work also showed that EMAP‐II is produced in various levels and that one can increase the sensitivity of tumor to TNF therapy in vivo by upregulating EMAP‐II production.…”
Section: Discussionmentioning
confidence: 60%
“…Its expression appears to increase the TNF receptor on tumor endothelium, and enhance the induction of tissue factor on endothelial cells, resulting in an antiangiogenic effect. It has been shown that in vivo sensitivity of the tumor vasculature to TNF is determined by the tumor production of EMAP‐II 48–50. This work also showed that EMAP‐II is produced in various levels and that one can increase the sensitivity of tumor to TNF therapy in vivo by upregulating EMAP‐II production.…”
Section: Discussionmentioning
confidence: 60%
“…EMAP-II is a 22 kDa proteolytically-cleaved fragment of AIMP1, first purified from conditioned medium of methycholoanthrene A-induced murine fibrosarcoma cells, and exhibiting endothelial cell (EC)-activating and monocyte pro-migratory properties [ 101 , 102 ]. EMAP-II overexpression renders TNF (tumor necrosis factor)-α-resistant soft tissue sarcoma sensitive to TNF-α therapy, and is dependent on TNF-receptor-1 relocalization from Golgi storage pools to the cell plasma membrane [103] , [104] , [105] . In prostate adenocarcinoma cells, chemotherapeutic agents induce EMAP II expression, thereby potentiating localized activation of host cell effector mechanisms, as well as anti-angiogenic and pro-apoptotic activities in melanoma lines [ 106 , 107 ].…”
Section: Variants Of Msc Constituents and Their Role In Cancer Progre...mentioning
confidence: 99%
“…Вплив на моноцити та ендотеліальні клітини проаналізовано більш детально для виявлення всіх молекулярних чинників цього процесу [6]. В ендотеліальних клітинах ЕМАР-ІІ викликає експресію Е-та Р-селектину, виділення фактора Віллебранда і продукування туморнекротичного фактора-альфа моноцитами [9].…”
Section: оригінальні дослідження в дитинстві та в осіб молодого віку ...unclassified